Does the German minimum wage help low income households? Evidence from observed outcomes and the simulation of potential effects - Teresa Backhaus; Kai-Uwe Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Does the federal minimum wage in Germany introduced in 2015 improve the income situation of low income households and reduce in-work poverty? Previous literature on its distributional impact was either focused on earnings and hourly wages (e.g. Caliendo et al., 2017), or is based on ex-ante simulations (e.g. Müller and Steiner, 2013). This paper provides systematic descriptive ex-post evidence on the distributional implications of the German minimum wage on wages and disposable household incomes as well as some underlying mechanisms. We analyze various measures of hourly wage and disposable household income distributions, both, for the group of affected individuals and the entire population. Most approaches identify individuals affected by the minimum wage based on pre-reform wages ignoring large job fluctuations and measurement error at the bottom of the wage distribution. In contrast, we define the group of affected by people's relative position in the wage distribution in each respective year. Full compliance scenarios are simulated at the actual and markedly higher minimum wage levels to interpret observational outcomes and gauge the redistributive potential of the minimum wage. We find evidence for wage increases at the bottom of the wage distribution. Effects on wage inequality are limited because of non-compliance, difficulties in hourly wage measurement in certain types employment, and unequal wage growth across the distribution. Confirming previous simulation evidence the minimum wage proves to be an ineffective tool for the redistribution of disposable household incomes. Overall inequality has even increased slightly as incomes of poor households grew below average. Affected households are not found primarily at the bottom, but rather in the middle of the income distribution. Working hours of individuals and earnings of other members in households affected by the minimum wage decreased. Benefit withdrawal is of minor importance as welfare transfers and top-up benefits were only marginally reduced by the minimum wage.
Keywords: J31; D31; J03; 330; minimum wage; wage distribution; income distribution